Analysis of Fundamental Factors and Systematic Risk on Stock Prices through Company Value in Mining Sector Companies on The Indonesia Stock Exchange - Simanjuntak, Luciana Kartini; Wibisono, Chablullah; Satriawan, Bambang (Jurnal Akuntansi, 2025)
This study aims to analyze the analysis of fundamental factors and systematic risk on stock prices through company value as an intervening variable in mining sector companies on the Indonesia Stock Exchange in this connection research on mining sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. The research method used is a quantitative approach with multiple linear regression analysis techniques and moderated regression processed using stata software. The results of the study indicate that ROA and PER have a positive and significant effect oni stocki prices, while DER and systematic risk do not have a significant effect. Simultaneously the four variables contribute significantly to stock price variations with an adjusted R² valuei of 15.3%. When the company value is entered as an intervening variable the adjusted R² value increases to 33.8%. The conclusion of this study confirms that fundamental factors and systematic risk are the main determinants in  creating stock prices, and their effectiveness depends on the company's ability to deal with systematic risks.